Plasmid pCBI carries genes for anaerobic benzoate catabolism in Alcaligenes xylosoxidans subsp. denitrificans PN-1. - Blake, C K (1987)
Pseudomonas sp. strain PN-1 is reclassified as Alcaligenes xylosoxidans subsp. denitrificans PN-1. Strain PN-1 is a gram-negative, rod-shaped organism, is motile by means of lateral flagella, is oxidase positive, and does not ferment sugars. Plasmid pCBI, carrying genes for the anaerobic degradation of benzoate in strain PN-1, is 17.4 kilobase pairs in length and is transmissible to a number of denitrifying Pseudomonas aeruginosa and Pseudomonas stutzeri strains. A restriction endonuclease map was constructed.